Catalytic Self‐Assembled Air Electrode for Highly Active and Durable Reversible Protonic Ceramic Electrochemical Cells. (25th September 2022) - He, Fan; Liu, Shuai; Wu, Tong; Yang, Meiting; Li, Wenhuai; Yang, Guangming; Zhu, Feng; Zhang, Hua; Pei, Kai; Chen, Yu; Zhou, Wei; Shao, Zongping
Abstract: Reversible protonic ceramic electrochemical cells (R‐PCECs) is one of the most promising devices for efficient energy conversion and storage due to the high flexibility in reversible operation on dual modes of fuel cell and electrolysis cells. The key limitations of R‐PCECs performance lie mainly in the sluggish catalytic activity and poor durability of the air electrode for oxygen evolution/reduction reactions under realistic operating conditions. Herein, the findings on the development of highly active and durable air electrodes, achieved by a catalytic self‐assembly of Ba2 Co1.5 Mo0.25 Nb0.25 O6− δ (BC1.5MN) composite electrode, are reported. Under high‐temperature firing conditions, BC1.5MN is elegantly decomposed to a single‐perovskite BaCoO3− δ (SP‐BCO) and a double‐perovskite Ba2− x Co1.5− x Mo0.5 Nb0.5 O6− δ (DP‐BCMN). Furthermore, fuel‐electrode‐supported full cells with BC1.5MN air electrode exhibit outstanding performance at 650 °C, achieving a peak power density of 1.17 W cm −2 and an electrolysis current density of 2.04 A cm −2 at 1.3 V. More importantly, the cells demonstrate excellent operation durability over 1100 h in fuel cell mode and exceptional cell cycling stability over 110 times within 220 h in dual modes of fuel cell and electrolysis cell. It is experimentally suggested that the catalytic durability is optimized by strong interaction between BCO and BCMN. Abstract : A catalytic Ba2 Co1.5 Mo0.25 Nb0.25 O6− δ (BC1.5MN) composite with a self‐assembled structure of SP‐BaCoO3− δ and DP‐Ba x Co1.5− x M0.25 N0.25 O6− δ is developed as an air electrode for reversible protonic ceramic electrochemical cells, demonstrating remarkable activity for oxygen reduction and evolution reaction, as well as exceptional cell cycling (220 h) and fuel‐cell (over 1100 h) stability.